An intervening sequence in an unusual histone H1 gene of Tetrahymena thermophila. - Wu, M (1986)
An intervening sequence of 254 base pairs interrupts the coding region of the single gene for macronuclear histone H1 of the ciliated protozoan, Tetrahymena thermophila. The intervening sequence has splice junctions similar to those found in RNA polymerase II genes of other organisms. No obvious similarities are observed between this intron and the self-splicing intervening sequence of the Tetrahymena ribosomal gene. The derived amino acid sequence describes a small extremely basic H1 protein missing most of the central hydrophobic domain that is conserved in all other H1 proteins. Macronuclei divide amitotically, without chromosome condensation, suggesting the conserved globular domain of H1 plays a role in higher-order chromatin structure.